2014
DOI: 10.4172/2329-6925.1000146
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine: A Possible Drug for Vascular Dementia

Abstract: Carnosine (β-alanyl histidine) is a small dipeptide with numerous beneficial effects, including the maintenance of the acid-base balance, antioxidant, chelating, anti-crosslinking, and anti-glycation activities in the living organism. High levels of carnosine are found in the skeletal muscles and in the brain. We have found that carnosine inhibits Zn2+-induced neuronal death, which plays acrucial role in the pathogenesis of vascular dementia. Our previous research demonstrated that carnosine participates in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…It is possible that compounds that regulate metal homeostasis and block amyloid channels may have potential for the treatment of neurodegenerative diseases. Indeed, we found that carnosine attenuates Zn 2+ -induced neurotoxicity [167]. Given that carnosine inhibits oligomerization and attenuates AβP-induced neurotoxicity [168] and PrP106-126-induced neurotoxicity [159], it may have therapeutic potential for amyloid diseases.…”
Section: Discussionmentioning
confidence: 73%
“…It is possible that compounds that regulate metal homeostasis and block amyloid channels may have potential for the treatment of neurodegenerative diseases. Indeed, we found that carnosine attenuates Zn 2+ -induced neurotoxicity [167]. Given that carnosine inhibits oligomerization and attenuates AβP-induced neurotoxicity [168] and PrP106-126-induced neurotoxicity [159], it may have therapeutic potential for amyloid diseases.…”
Section: Discussionmentioning
confidence: 73%